The event of the thing : Derrida's post-deconstructive realism - Marder, Michael, 1980- (University of Toronto Press, 2009)
The Event of the Thing is the most complete examination to date of Derrida's understanding of thinghood and its crucial role in psychoanalysis, ethics, literary theory, aesthetics, and Marxism.